EFEKTIFITAS SANKSI PIDANA DALAM PERATURAN DAERAH PROVINSI JAMBI TENTANG PAJAK DAERAH - M. Chairul Idrah (Jurnal Ilmiah Universitas Batanghari Jambi, 2014)
As the main legal instruments at the regional level, the Regional Regulation regulate matters relating to the affairs of government under the authority of the area based on the dynamics and aspirations of the people. Thus, local regulation is not solely justify the power of local governments to act and regulate its citizens, but also provides protection of the rights and interests of the community luas.Untuk give enforcement power, local regulation may contain both legal sanctions of criminal law, administrative law or civil law. One of the regulation of blood products is Jambi Provincial Regulation on Local Taxes. In the field of practice Jambi province receives from local tax revenues exceed specified targets but still the weaknesses number of taxpayers who do not pay the tax themselves based on awareness and volunteerism it is certainly an impact on the financial losses of the taxpayer daerah.kealfaan are criminal sanctions set out in the Regulations which does not provide a deterrent against dutifully pay local taxes.Keyword :  Effectively, Regulation and Criminal Sanctions